ประสิทธิผล ของการใช้แนวปฏิบัติทางคลินิกสำหรับการป้องกันภาวะสับสนเฉียบพลันในผู้ป่วยวิกฤต หอผู้ป่วยหนักอายุรกรรม โรงพยาบาลลำปาง - สุกัญญา เลาหธนาคม (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Delirium is a common syndrome after patients areconfined in an intensive care unit (ICU). The impact of delirium in an ICU can be life-threatening due to behavioral changes in the patient. Prevention of ICU delirium needs practices based on evidence in order to achieve positive outcomes. The purpose of this operation study was to determine the effectiveness of implementing clinical practice guidelines (CPGs) for prevention of ICU delirium in the medical intensive care unit (MICU), Lampang Hospital. Subjects included 82 conscious and able to communicate critically ill patients,who were confined inthe MICU before implementing of CPGsduring September to November 2013,and 70 subjects who were confined in the MICU afterimplementing of CPGs from JanuarytoMarch 2014. The instruments used in this study were CPGs for prevention of delirium among critically ill patients of Lampang Hospital developed by Laohatanakom and colleague(2012) and an outcome evaluation form, also developed by Laohatanakom and colleague (2012). The study was based on the CPGs implementing framework of the Australian National Health and Medical Research Council (NHMRC, 1999). Data analysis was done using descriptive statistics. The finding revealed that the incidence rate of ICU delirium among subjects in the non CPGs group was 34.15% while the incidence rate of ICU delirium among subjects in the CPGs group was only 12.86%. The finding of this study confirmed that implementing the CPGs inthe MICU, Lampang Hospitalwas ableto reduce the incidence rate of ICU delirium. The investigator suggests that these CPGs should be incorporated with quality improvement activities among other ICUs as well.